2017
DOI: 10.1002/hbm.23593
|View full text |Cite
|
Sign up to set email alerts
|

Brain structure and organization five decades after childhood onset epilepsy

Abstract: The purpose of this project was to characterize brain structure and organization in persons with active and remitted childhood onset epilepsy 50 years after diagnosis compared to healthy controls. Participants from a population-based investigation of uncomplicated childhood onset epilepsy were followed up 5 decades later. Forty-one participants had a history of childhood onset epilepsy (mean age of onset= 5.2 yrs, current chronological age= 56.0 yrs) and were compared to 48 population-based controls (mean age=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Although regional and network-based analyses were performed using the same morphological data (i.e., volumetric data), the nature of graph theory analyses provided another view of morphometric data that rendered additional insights regarding how the cognitive phenotypes differed in their morphological associations. This same pattern was observed in a cohort of patients with uncomplicated childhood onset epilepsies 50 years after their diagnosis ( Garcia-Ramos et al, 2017 ), where graph theory analyses of the morphological networks revealed subtleties missed by conventional regional analyses. Further, Reyes et al (2019) recently demonstrated that TLE patients with an isolated language impairment showed unremarkable regional analyses but differences in network structure using graph theory analysis ( Reyes et al, 2019 ).…”
Section: Discussionsupporting
confidence: 71%
“…Although regional and network-based analyses were performed using the same morphological data (i.e., volumetric data), the nature of graph theory analyses provided another view of morphometric data that rendered additional insights regarding how the cognitive phenotypes differed in their morphological associations. This same pattern was observed in a cohort of patients with uncomplicated childhood onset epilepsies 50 years after their diagnosis ( Garcia-Ramos et al, 2017 ), where graph theory analyses of the morphological networks revealed subtleties missed by conventional regional analyses. Further, Reyes et al (2019) recently demonstrated that TLE patients with an isolated language impairment showed unremarkable regional analyses but differences in network structure using graph theory analysis ( Reyes et al, 2019 ).…”
Section: Discussionsupporting
confidence: 71%
“…Epileptic activity can induce excitotoxic damage locally, but it can also propagate through white matter tracts and damage distant areas, including areas that are contralateral to the focus (Feldt Muldoon et al, 2013 ; Burns et al, 2014 ; Caciagli et al, 2014 ; Xu et al, 2014 ). For example, complex partial seizures in patients with epilepsy were found to begin at abnormal hippocampal synapses in the middle temporal lobe (Colder et al, 1996 ) and were found to propagate through the hippocampal network to cause temporal lobe epilepsy (Garcia-Ramos et al, 2017 ; Lupica et al, 2017 ). This propagation can cause a pathological restructuring of the affected networks by increasing synaptogenesis that facilitates the development and spread of seizure activity (Fidzinski et al, 2015 ; Heller and Rusakov, 2015 ; Amakhin et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies between structural and functional connectivity have produced mixed results and demonstrate imperfect correspondence: at best half of the variance in functional connections is explained by structure (Suárez et al, 2020 ). In the literature, co-occurring alterations in thalamus morphometry and network topology have only been reported in epilepsy (Garcia-Ramos et al, 2017 ; Lee et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%